Effectiveness of mobile-based educational interventions on quality of life among osteoarthritis patients: A quasi-experimental study - Agung Widiastuti; Purwidodo; Ady Irawan. AM; Carissa Putri Maharani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Osteoarthritis (OA) is a chronic musculoskeletal disorder that substantially reduces physical function, mobility, and psychosocial well-being among older adults. Limited health literacy and restricted access to continuous education often hinder effective self-management and worsen quality of life. Mobile-based health education has emerged as a practical approach to improve patient engagement and self-care behaviors. This study aimed to evaluate the effectiveness of a mobile-based educational intervention in improving the quality of life among patients with osteoarthritis in the working area of the Baki Health Center, Sukoharjo. Research Methodology: This study employed a quasi-experimental pretest–posttest control group design. A total of 50 osteoarthritis patients were recruited using purposive sampling and divided equally into intervention (n=25) and control (n=25) groups. The intervention group received mobile-based education for 4 weeks, including osteoarthritis management materials, pain assessment, physical activity guidance, nutrition monitoring, reminders, and chatbot support, while the control group received standard care. Quality of life was measured using the validated SF-36 questionnaire before and after the intervention. Data were analyzed using paired sample t-tests with significance set at p<0.05. Results: The intervention group demonstrated a significant improvement in quality-of-life scores from pretest to posttest (37.60 ± 14.95 vs. 70.20 ± 10.79; t = −10.373; p < 0.001) with a very large effect size (Cohen’s d = −2.075). In contrast, the control group showed no statistically significant change (36.00 ± 9.87 vs. 36.12 ± 10.24; t = −0.486; p = 0.632; Cohen’s d = −0.097). Conclusion: Mobile-based educational interventions were effective in improving the quality of life of patients with osteoarthritis. Integrating mobile health education into primary healthcare services may strengthen self-management, increase patient independence, and support long-term chronic disease management among older adults.